2019
DOI: 10.1186/s40902-019-0237-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of considering revision rhinoplasty in Saudi patients and its associated factors

Abstract: Background: Primary rhinoplasty outcomes may not meet individual expectations. Consequently, reoperation may be advocated to improve results. This study examines the prevalence of individuals considering revision rhinoplasty, while identifying the main cosmetic and functional complaints and factors associated. Methodology: This is a cross-sectional study conducted in Saudi Arabia using a self-reported online questionnaire distributed through social media channels. The sample included 1370 participants who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Which is almost identical with Kazemy's result [14]. It is on contrary with study conducted to Alsubeeh and her colleagues [13]. Over and above that the study conducted to Loghmani and her colleagues demonstrated that more than half of the high school girls in Kerman, Iran were interested to undergo rhinoplasty.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Which is almost identical with Kazemy's result [14]. It is on contrary with study conducted to Alsubeeh and her colleagues [13]. Over and above that the study conducted to Loghmani and her colleagues demonstrated that more than half of the high school girls in Kerman, Iran were interested to undergo rhinoplasty.…”
Section: Discussionsupporting
confidence: 68%
“…Pursuant to the Association of American Plastic Surgeons, 3.8 million cosmetic surgeries were performed from 2003 to 2012, which compared to 1997, 299% increased [12]. In Middle East countries such as Saudi Arabia, Rhinoplasty recently representing 30% of all aesthetic procedures [13]. As well as, the neighboring countries such as Iran is a top ranked globally in the world regard to the number of cosmetic surgeries; therefore, among cosmetic surgeries tendency to Rhinoplasty also in Iran is more than other countries [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Appearance is an important part of a person's identity and affects the way that he or she interacts with others in social situations (Hashemi et al, 2017). The configuration of the human nose contributes to the beauty and symmetry of the face and is usually the most prominent feature of the face (Alsubeeh et al, 2019). Therefore, undergoing a rhinoplasty can dramatically change a person's appearance (Klassen et al, 2016).…”
mentioning
confidence: 99%
“…A rhinoplasty is a surgical procedure that reconstructs the shape of an individual's nose while either maintaining or improving the individual's airway function (Alsubeeh et al, 2019). The goal of the surgeon performing the procedure is to improve the appearance of the individual's nose as well as its function (Manhas et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation